Respon Eskplan Biji Gaharu (Aquilaria malaccencis Lamk.) terhadap Pemberian NAA dan IBA Secara In Vitro - Romasli Nadeak; Nelly Anna; Edy Batara Mulya Siregar (Peronema Forestry Science Journal, 2012)
Agarwood is non-wood forest product with high number of economic because the wood has many benefits. The presence of gaharu in nature is endangered because of illegal logging and for development of agarwood needed seed quality supplying, one with tissue culture. This study aims to determine the response of seed explants A. malaccensis and determine the concentration of the best NAA and IBA for induction of callus. This research use Complete Random Design (RAL) with 2 Growth  Regulator NAA and IBA in any concentrates with agarwood seed explants. Results showed that callus was obtained as response of  agarwood seed explants with NAA and IBA and the concentrate that’s have real an effect on to determine the time of callus appear with best concentrate was NAA 2 ppm dan IBA 2 ppm. Callus appear dominated by olive green and green brown color, meanwhile tekstur of callus dominated by compact node. Keywords: Agarwood, Callus, NAA, IBA, in vitro